Nie tylko klawisz, nie tylko ment – z historii kilku socjolektalnych nazw policjantów i funkcjonariuszy więziennych - Pacuła, Jarosław (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2020)
The author presents several nouns functioning as synonyms for jailer (warder) and policeman. The author pays attention to these names because descriptions of contemporary language of deviant circles are frequent, but the vocabulary of criminals still doesn’t have diachronic characteristics. The described names are, among others: klawisz / klawisznik [jailer, screw], ment [louse], chmura [cloud], jancio [Johnny]. The author describes name changes in Polish prison slang from the late nineteenth and early twentieth century. He indicates the sources of individual names and describes the semantic changes that took place under the influence of foreign languages as well.